2019
DOI: 10.1002/ajb2.1233
|View full text |Cite
|
Sign up to set email alerts
|

Non‐native insects dominate daytime pollination in a high‐elevation Hawaiian dryland ecosystem

Abstract: PREMISE OF THE STUDY:Over one-third of the native flowering plant species in the Hawaiian Islands are listed as federally threatened or endangered. Lack of sufficient pollination could contribute to reductions in populations, reproduction, and genetic diversity among these species but has been little studied. METHODS:We used systematic observations and manual flower treatments to quantify flower visitation and outcrossing dependency of eight native (including four endangered) plant species in a dryland ecosyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 76 publications
1
14
0
Order By: Relevance
“…We verified that these insect taxa transported the pollen of the focal plants, as described above. Although flower visitation does not equate to pollination, our prior work with breeding system floral treatments (e.g., bagging of flowers) found that flowers of each of the species in this experiment produced increased seed set when exposed to the visitor community, relative to flowers that were bagged to prevent outcrossing (Aslan et al, 2019); note that this increase was significant for all plant species except S. lanceolata .…”
Section: Methodsmentioning
confidence: 72%
See 3 more Smart Citations
“…We verified that these insect taxa transported the pollen of the focal plants, as described above. Although flower visitation does not equate to pollination, our prior work with breeding system floral treatments (e.g., bagging of flowers) found that flowers of each of the species in this experiment produced increased seed set when exposed to the visitor community, relative to flowers that were bagged to prevent outcrossing (Aslan et al, 2019); note that this increase was significant for all plant species except S. lanceolata .…”
Section: Methodsmentioning
confidence: 72%
“…Reproduction of our focal plant species is likely to be negatively affected by decreased pollinator interactions, based on our previous work in the system. Both common and endangered plant species are pollen limited, and flower treatment experiments showed that open‐pollinated flowers produced significantly more seed than bagged flowers for all of our focal plant species except S. lanceolata (Aslan et al, 2019). In general, then, these focal plants have limited autogamy, or self‐fertilization, and are dependent to some degree on pollinators for reproductive fitness.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Introduced mammals reduce Hawaiian seedling recruitment directly through consumption of flowers, seeds, and seedlings (Pender, Shiels, Bialic‐Murphy, & Mosher, 2013; Shiels & Drake, 2011; Shiels, Pitt, Sugihara, & Witmer, 2014), as well as indirectly through disturbance to the plant‐growth substrate (Cole, Litton, Koontz, & Loh, 2012; Murphy, Inman‐Narahari, Ostertag, & Litton, 2014). Non‐native insects may similarly threaten seedling recruitment indirectly through damage to flowers or through failure to pollinate native plants (Aslan, Shiels, Haines, & Liang, 2019; Aslan, Zavaleta, Tershy, Croll, & Robichaux, 2014). Invasive slugs and snails also target native seedlings directly for consumption in Hawaiian forests (Joe & Daehler, 2008; Shiels, Ennis, & Shiels, 2014).…”
Section: Introductionmentioning
confidence: 99%